PERFORMANCE OF COW DUNG-DERIVED BIOGAS AS A SUSTAINABLE COOKING FUEL - Gana, Abdullahi Hassan; Sa’id, Idris A. (FUDMA Journal of Sciences, 2025)
The rising demand for sustainable energy solutions has accelerated the search for low-cost, renewable, and eco-friendly cooking fuels. This study evaluated the performance of biogas derived from cow dung as a potential domestic energy source using a laboratory-scale batch anaerobic digestion system. Fresh cow dung was homogenized with water at a ratio of 4.5:20 (w/v) and introduced into a 25-liter high-density polyethylene (HDPE) digester fitted with inlet and outlet valves and linked to a gas storage unit. The system operated under mesophilic conditions for eight days, during which ambient temperature and daily gas yield were monitored. Biogas generation was negligible during the initial three days (0.00–0.018 kg), representing a lag phase in microbial activity. From Day 4 onward, production increased steadily, peaking at 9.09 kg on Day 8. Regression analysis demonstrated a strong positive correlation between retention time and biogas yield (R² = 0.94, p < 0.001), whereas temperature exhibited no significant influence (r = –0.08, p = 0.86). These results indicate that cow dung serves as a reliable substrate, capable of sustaining biogas production even under natural temperature variations. The findings confirm the viability of cow dung-derived biogas as a sustainable cooking fuel, particularly for rural households. Adoption of this technology can reduce dependence on firewood and kerosene, mitigate environmental degradation, and improve household air quality. Moreover, the use of inexpensive, locally available materials for digester construction highlights its practicality for widespread application in resource-limited communities.
Keywords: Anaerobic digestion; Biogas production; Cow dung; Renewable cooking fuel; Sustainable energy